Tinjauan Awal Pengaruh Lingkungan Dalam Pemilihan Cekungan Wonosari Sebagai Lokasi Hunian - nfn Harriyadi (Berkala Arkeologi, 2020)
Wonosari Basin is a plateau area and has been inhabited by humans continuously. This research goal is to determine the environmental factors that considered by humans to settle in Wonosari Basin in proto-history until Hindu-Buddhist period. Data used in this study are proto-history and Hindu-Buddhist sites distribution in Wonosari Basin. Analysis is conducted by spatial approach through map overlaying between sites distribution and environmental variable such as water source, slope, soil, and rock formation. This study shows that Wonosari Basin has been selected by human to settle because it has greater water source compared to other landform area in Gunung Sewu. In addition, Wonosari Basin has large flat area which simplify accessibility to utilize natural resource.